Effects of Leaf Cutting on Fusarium Head Blight Disease Development, Photosynthesis Parameters and Yield of Wheat under F. graminearum Inoculation Condition - Qianglan Huang (MDPI AG, 2021)
Fusarium head blight (FHB), caused by Fusarium graminearum, occurs mainly on developing wheat seeds, which are important energy sinks. Leaf cutting (removing a portion of the energy sources) could have an effect on the damage caused by F. graminearum. To determine the effects of leaf cutting on disease development, photosynthesis parameters, and yield components between resistant and susceptible wheat genotypes, the wheat FHB-resistant line L693 and FHB-susceptible line L661, which have similar genetic backgrounds, were used in this study. Different numbers of leaves were removed before inoculation with F. graminearum, and photosynthesis parameters, including the net photosynthesis rate (Pn), stomatal conductance (Gs), and intercellular CO2 concentration (Ci), were measured at various time points both before and after F. graminearum infection. The number of diseased spikelets (NDS) and yield components were also measured. The greenhouse and field experiments results showed that cutting leaves could decrease the NDS and alleviate the damage from FHB, which could partly compensate for the yield loss caused by F. graminearum under F. graminearum inoculation condition. Leaf cutting did not significantly change the total grain weight per spike (GWS) after F. graminearum inoculation in both L661 and L693. Further study found that the Pn obviously differed between L661 and L693 after infection with F. graminearum and cutting leaves could aggravate the Pn difference between L661 and L693, which revealed cutting leaves could change the balance between source and sink, with the change of Pn, which may refer to FHB resistance. This study provides new insights into both energy sources and sinks for future studies on the physiological mechanism underlying systematic resistance against FHB.